PENGARUH CSR DAN INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN - Edwin Wibisono; Rosinta Ria Panggabean (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2019)
The purpose of the study is to know the relationship between the independent variables CSR and VAIC (Intellectual Capital) on the dependent variable, which is financial performance measured by using ROA, ROE, PER, and EPS. This study took the data of manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017. There were 152 manufacturing companies, and after making sample selections, there were 115 companies left. In analyzing the statistics data of this research, the author uses the Eviews application program. The results showed that the significant effect only occurred on the independent variable VAIC on the EPS dependent variable. It was suggested that companies should pay more attention to and maximize intellectual capital owned, and pay more attention to CSR more seriously.